KEMAMPUAN MAHASISWA CALON GURU MATEMATIKA DALAM MENYELESAIKAN SOAL OLIMPIADE MATEMATIKA PADA MATERI ALJABAR DAN GEOMETRI - Ulil Nurul Imanah (Journal of Mathematics Education and Science, 2021)
This study aims to determine the ability of pre-service mathematics teachers to solve mathematics olympiad questions on algebra and geometry. This research is quantitative descriptive. The research subjects were mathematics education students at the Faculty of Teacher Training and Education at Majapahit Islamic University in semester V of the 2020-2021 academic year who had completed Mathematical Problem-Solving courses. The subjects that study mathematical problem-solving strategies and deepen elementary and secondary mathematics olympiad problems. The research subjects were 14 people. The instrument used was four questions at the high school level mathematics olympiad, consisting of 2 questions about algebra and two questions about geometry. Based on the results of the study, it was concluded that the ability of pre-service mathematics teachers in the Mathematics Education Study Program of the Faculty of Teacher Training and Education, Majapahit Islamic University in solving math Olympiad questions on algebra and geometry was in the sufficient category with an average score of 57.68 Abstrak Penelitian ini bertujuan untuk mengetahui kemampuan mahasiswa calon guru matematika dalam menyelesaikan soal olimpiade matematika pada materi aljabar dan geometri. Penelitian ini merupakan penelitian deskriptif kuantitatif. Subyek penelitian adalah mahasiswa pendidikan matematika Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Majapahit semester V tahun akademik 2020-2021 yang telah menyelesaikan perkuliahan Pemecahan Masalah Matematika, yaitu mata kuliah yang mempelajari tentang strategi pemecahan masalah matematika dan mendalami soal-soal olimpiade matematika tingkat dasar dan menengah. Subyek penelitian berjumlah 14 orang. Instrumen yang digunakan adalah 4 soal olimpiade matematika tingkat sekolah menengah, yang terdiri dari 2 soal materi aljabar dan 2 soal materi geometri. Berdasarkan hasil penelitian diperoleh simpulan bahwa kemampuan mahasiswa calon guru matematika di Prodi Pendidikan Matematika FKIP Universitas Islam Majapahit dalam menyelesaikan soal olimpiade matematika pada materi aljabar dan geometri berada pada kategori cukup dengan nilai rata-rata 57,68.